Investigating English Students` Vocabulary Learning Strategies at Raden Intan State Islamic University - Kurniawan, Iwan; Roza, Melinda; Juhana, Juhana (English Education: Jurnal Tadris Bahasa Inggris, 2021)
The purpose of this study was to determine the types of Vocabulary Learning Strategies (VLS), the most and least frequently used VLSs by female and male students, and the types of VLSs chosen to address vocabulary learning problems. This study employed a survey technique. The population for this study was drawn from Lampung State Islamic University's English Education Department, which consisted of three classes and had a total enrollment of approximately 75 students. Female students totaled 64, while male students totaled 11. The sample consisted of fourth-semester students. The instrument used in this study was a questionnaire that Gu and Johnson proposed in 1996. Interviews were also used as a tool. All English department students at Lampung State Islamic University used one of four vocabulary learning strategies. Among the four categories of Vocabulary Learning Strategies, students in the three classes favoured metacognitive strategies the most, as indicated by the mean score (2.90). On the other hand, the least frequently used strategy was memory/repetition, as indicated by the lowest mean score (2.22). Female students tended to use metacognitive strategies, as indicated by their highest mean score (2.87), while male students tended to use memories/repetition strategies, as indicated by their average score (2.2). Additionally, the most frequently used strategy by male students was metacognitive strategy with a mean score of (2.93), while the least frequently used strategy was activation with a mean score of (2.93). (2.31). To overcome the problem of vocabulary acquisition, the students used the strategies of consulting a dictionary first, followed by learning grammar and asking other people second. The final strategies used were word practise and internet surfing.